The perception of reasons of relapse among drug addicts: ways to overcome - Mohamad, Mardiana; Dzulkifli, Mariam Adawiah; Abd Rahman, Wan Rafaei; Sheik Dawood, Shariffah Rahah (2011)
A longitudinal study conducted by the National Institute of Drug Abuse (NIDA) in the United States (2007) has affirmed that re-establishment of ex-drug addicts’ relationship with family, and significant others are important part of the recovery process as well as relapse prevention. In the Malaysian context, the National Anti-drug Addiction Agency (2007) has reported that once the rehabilitated addicts leave the rehabilitation centers, there is often a lack of community support for them to live independently of drugs, hence leading to potential relapse. Therefore, in attempt to understand the reasons of relapse, especially from the drug addicts’ own perspectives, face-to-face interviews were conducted on 263 Malay, Chinese and Indian drug addicts in several rehabilitation centres in Malaysia. The objective is to explore their perception of the reasons of relapse. The analysis of their responses showed that the three ethnic groups of addicts in the study mentioned more or less similar reasons for their relapse. These include peer influence or pressure; rehabilitation programmes; relationship problem; and boredom. The paper attempts to propose mechanisms that can be used to overcome the problem of relapse among drug addicts in Malaysia.